Pengaruh Kebijakan Hutang dan Profitabilitas Terhadap Nilai Perusahaan - Aulia Rahma Khusnul Khotimah; Anggi Saktiya Pratiwi; Yeni Lestari Simbolon; Wildan Yudhanto; Yacobo P. Sijabat (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
A company definitely aims to make a profit. The company also has a purpose to prosper the owners by maximizing the value of the company. The higher the value of a company will reflect that it has high prosperity for stock owners. This study was conducted with the aim of providing empirical evidence of the influence of debt and profitability policies on corporate value in agricultural sector companies listed on the IDX for the 2019-2021 period. This study uses the population of agricultural sector companies recorded on the IDX in 2019-2021. Then the use of samples obtained by adopting purposive sampling method. Descriptive statistical test method and multiple linear regression test into data analysis techniques in this study. This study gives the result that the debt policy and profitability have no influence on the variable value of the company.